2022
DOI: 10.1101/2022.09.02.506332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 nucleocapsid protein inhibits the PKR-mediated integrated stress response through RNA-binding domain N2b

Abstract: The nucleocapsid protein N of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enwraps and condenses the viral genome for packaging but is also an antagonist of the innate antiviral defense. It suppresses the integrated stress response (ISR), purportedly by interacting with stress granule (SG) assembly factors G3BP1 and 2, and inhibits type I interferon responses. To elucidate its mode of action, we systematically deleted and over-expressed distinct regions and domains. We show that N via domain N2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…The SARS-CoV-2 nucleocapsid, like nucleocapsids of other Betacoronaviruses, is a highly multifunctional protein. Like other coronavirus nucleocapsids, it is thought to play key roles in the packaging of viral RNA 25 , the production of viral RNA through interactions with the replication-transcription complex 1013 , and the antagonism of the innate immune response 2628 . To better understand why the N: G215C mutation was important at a molecular level, we looked at where in the viral life cycle the stably dimerized form of N was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The SARS-CoV-2 nucleocapsid, like nucleocapsids of other Betacoronaviruses, is a highly multifunctional protein. Like other coronavirus nucleocapsids, it is thought to play key roles in the packaging of viral RNA 25 , the production of viral RNA through interactions with the replication-transcription complex 1013 , and the antagonism of the innate immune response 2628 . To better understand why the N: G215C mutation was important at a molecular level, we looked at where in the viral life cycle the stably dimerized form of N was observed.…”
Section: Resultsmentioning
confidence: 99%
“…All variants triggered ISR activation, but Delta induced significantly less phosphorylation of PKR and eIF2α than the ancestral strain and Omicron. It has been suggested that the SARS-CoV-2 N protein can inhibit PKR activation by sequestering dsRNA [24, 54] and adaptations in the Delta N protein might make this process more efficient. Omicron on the other hand induces similar levels of p-PKR but increased levels of p-eIF2α, indicating stronger ISR activation.…”
Section: Discussionmentioning
confidence: 99%